2002
DOI: 10.1093/oxfordjournals.molbev.a004138
|View full text |Cite
|
Sign up to set email alerts
|

α1,4-Fucosyltransferase Activity: A Significant Function in the Primate Lineage has Appeared Twice Independently

Abstract: In the animal kingdom the enzymes that catalyze the formation of alpha1,4 fucosylated-glycoconjugates are known only in apes (chimpanzee) and humans. They are encoded by FUT3 and FUT5 genes, two members of the Lewis FUT5-FUT3-FUT6 gene cluster, which had originated by duplications of an alpha3 ancestor gene. In order to explore more precisely the emergence of the alpha1,4 fucosylation, new Lewis-like fucosyltransferase genes were studied in species belonging to the three main primate groups. Two Lewis-like gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Then a third conserved motif of six amino acids was called the acceptor motif ((I/V/ F)HH(R/W)(D/E)(I/V/L)), because a single amino acid change (Trp 111 3 Arg) was able to transform the type 1 ␣1,4-fucosylation of FUT3 (leading to the Le a epitope) into the type 2 ␣1,3-fucosylation (leading to the Le x epitope) (46,47). A fourth conserved motif, located on the NH 2 -terminal side of the sequence, before the acceptor motif, was later called motif III (12,47), giving the following order for these four conserved motifs: III, acceptor motif, I and II. Finally, while writing the present paper, we found a fifth conserved motif located between the acceptor motif and motif I.…”
Section: Conserved Peptide Motifs Of Fut10 and Fut11-mentioning
confidence: 99%
“…Then a third conserved motif of six amino acids was called the acceptor motif ((I/V/ F)HH(R/W)(D/E)(I/V/L)), because a single amino acid change (Trp 111 3 Arg) was able to transform the type 1 ␣1,4-fucosylation of FUT3 (leading to the Le a epitope) into the type 2 ␣1,3-fucosylation (leading to the Le x epitope) (46,47). A fourth conserved motif, located on the NH 2 -terminal side of the sequence, before the acceptor motif, was later called motif III (12,47), giving the following order for these four conserved motifs: III, acceptor motif, I and II. Finally, while writing the present paper, we found a fifth conserved motif located between the acceptor motif and motif I.…”
Section: Conserved Peptide Motifs Of Fut10 and Fut11-mentioning
confidence: 99%
“…To date, FucT enzymes that display ␣1,4 activity have also been found in the chimpanzee (48), Rhesus macaque (Old World Monkey) (49), and plants (50,51). According to sequence alignment, all of these FucTs contain a tryptophan residue within the N-terminal hypervariable stem region, which was found to be essential for conferring ␣1,4 activity in mammalian FucTs (18).…”
Section: Ua948mentioning
confidence: 99%
“…None of the chacma baboons in this study have shown the presence of Le a antigen, confirming previously reported data. The fucosyltransferase encoding genes for rhesus macaques and squirrel monkey were sequenced in 2002, 26 and homologous sequences were found for rhesus macaques but not for squirrel monkeys, meaning that functional alpha 3/4-fucosyltransferases could be present in OWMs and absent in NWMs. This may justify the absence of Le antigens in all the squirrel monkeys tested in this study.…”
Section: Discussionmentioning
confidence: 99%